11w+3t-4w-5t=

Simple and best practice solution for 11w+3t-4w-5t= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11w+3t-4w-5t= equation:


Simplifying
11w + 3t + -4w + -5t = 0

Reorder the terms:
3t + -5t + 11w + -4w = 0

Combine like terms: 3t + -5t = -2t
-2t + 11w + -4w = 0

Combine like terms: 11w + -4w = 7w
-2t + 7w = 0

Solving
-2t + 7w = 0

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-7w' to each side of the equation.
-2t + 7w + -7w = 0 + -7w

Combine like terms: 7w + -7w = 0
-2t + 0 = 0 + -7w
-2t = 0 + -7w
Remove the zero:
-2t = -7w

Divide each side by '-2'.
t = 3.5w

Simplifying
t = 3.5w

See similar equations:

| a*h=15 | | 4x+12=48 | | 5x+18-4x=-3-12 | | 6v^2+30v=0 | | 5x^2+34x-7=0 | | 19+y=42 | | 2=x-2 | | 30-15=7+x | | 4(g+3)=24 | | 2(w+1)=10 | | 49y^2-225=0 | | -6(x+2)-10=29+3 | | 5x-3=13x-25 | | 8x-9=-41 | | 20+x=80 | | 66-9a=(19-3a) | | y-5=7 | | -2b=-15 | | 11x^2-121x=0 | | 6x-6=54 | | 3(13-2q)=-3+q | | 27x^2-29x+0=0 | | 4a+(-3)=13 | | 10-2y=32 | | x-(-6-9x)+50=56 | | 4X+2=5x+1 | | 27x^2-29x=0 | | 8s-5=9+s | | 3z+6=9 | | 5n+-3=32 | | x+3=13-19x | | -3+5n=32 |

Equations solver categories